The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1989
DOI: 10.1073/pnas.86.3.930
|View full text |Cite
|
Sign up to set email alerts
|

Species distribution of a phosphoprotein (parafusin) involved in exocytosis.

Abstract: A cytosolic phosphoprotein that appears to function in membrane fusion during exocytosis of secretory products has previously been isolated from Paramecium tetraurelia. This phosphoprotein, parafusin, with Mr 63,000, is rapidly dephosphorylated via a Ca2-dependent process when secretagogues induce exocytosis in competent cells. Dephosphorylation does not occur in exocytosis-incompetent cells. Polyclonal antibodies against purified parafusin have now been used to show that this protein is present in unicellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…During two-dimensional gel electrophoresis and autoradiography we consistently lost the first spot during SDS/ PAGE. Interestingly, the 32P label also was completely lost, probably for the same reason, with the isolation protocol used by Satir et al (1989), although the antibodies that they prepared against this form recognize the phosphorylated 63 kDa band on blots from SDS/PAGE. Altogether, their data may be difficult to compare with ours, since the antibodies that we prepared were against the well-defined spot of pI 5.95 of 63 kDa.…”
Section: Isoforms Of Pp63mentioning
confidence: 99%
See 2 more Smart Citations
“…During two-dimensional gel electrophoresis and autoradiography we consistently lost the first spot during SDS/ PAGE. Interestingly, the 32P label also was completely lost, probably for the same reason, with the isolation protocol used by Satir et al (1989), although the antibodies that they prepared against this form recognize the phosphorylated 63 kDa band on blots from SDS/PAGE. Altogether, their data may be difficult to compare with ours, since the antibodies that we prepared were against the well-defined spot of pI 5.95 of 63 kDa.…”
Section: Isoforms Of Pp63mentioning
confidence: 99%
“…Since a phosphatase system is located in the cell cortex , this might account for the loss Of 32P label from cortices and for the selective detectability of PP63 in supernatants by gel autoradiography, whereas detection by antibodies is less ambiguous. Satir et al (1989) suggested the occurrence of a Ca2+_ dependent sedimentable pool which had previously remained undetected. Yet we found no indications of Ca2+ binding by P63 or PP63 (see the Results section).…”
Section: Localization Of P63/pp63mentioning
confidence: 99%
See 1 more Smart Citation
“…Parafusin shows immunological cross-reactivity with proteins from a variety ofunicellular organisms and cells of metazoan groups of wide evolutionary divergence, as well as with rat tissues, including brain, heart, pituitary, and kidney. These results suggest that parafusin was present early in the history of eukaryotes and may be of functional importance in the general mechanism of exocytosis and membrane fusion (7,8).A Mr 62,000 phosphoglycoprotein in liver that possessed an a-glucose-l-phosphate (aGlc-l-P) moiety linked to a short chain of mannoses that was O-linked to a senine residue of the protein was independently discovered (9). The bond between glucose and mannose in this protein was a phosphodiester linkage formed by the action of a unique aGlc-1-P phosphotransferase (9).…”
mentioning
confidence: 99%
“…The coincidence of exocytosis competence and pp63/pf N de-phosphorylation led to the proposal that this protein may govern membrane fusion, from which the name was derived [30][31][32]. Cloning of its homologue in Tetrahymena and disruption of its single pp63/pf gene suggested this not to be the case [33].…”
Section: Introductionmentioning
confidence: 99%